Composite ceramic powder for high expansion, low dielectric and low loss LTCC substrate and its preparation method
By using composite porcelain powder composed of 50-60 wt% borosilicate glass powder and 40-50 wt% calcium borosilicate glass powder, the problem of difficult to achieve high thermal expansion coefficient, low dielectric constant and low dielectric loss in the prior art is solved, and the dielectric performance and thermal expansion performance are optimized, and the sintering temperature is reduced.
Patent Information
- Application Number
- CN202211577633.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The prior art is difficult to simultaneously realize LTCC substrate materials or composite porcelain powder with high thermal expansion coefficient, low dielectric constant and low dielectric loss, and there are problems of complex raw material composition and high sintering temperature.
A composite porcelain powder for high expansion, low dielectric, low loss, LTCC substrates is provided, including 50-60 wt% borosilicate glass powder and 40-50 wt% calcium borosilicate glass powder. Both are amorphous and have a particle size between 1.0-2.5 μm. Through specific composition and preparation methods, the use of additional nucleation agents and ceramic phases are avoided.
Excellent dielectric properties with a dielectric constant between 4.2-5.0 and a dielectric loss of 0.001-0.002@12-15GHz, as well as a high thermal expansion performance with a thermal expansion coefficient of (11-12)×10-6/℃, and dense sintering at a lower sintering temperature (870-900℃).
Smart Images

Figure CN115849708B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a composite ceramic powder for a high expansion, low dielectric and low loss LTCC substrate and a preparation method thereof. Background Art
[0002] One of the keys to the preparation technology of low temperature co-fired ceramic (LTCC) substrates and their RF components is to have ceramic powders with particularly excellent performance that can be used to prepare cast tapes, which are generally composite powders of ceramics and glass. Depending on the application, LTCC substrates and their corresponding ceramic powders are required to have different properties, such as high strength, high or low thermal expansion coefficients, and high thermal conductivity. One of the development directions of LTCC substrates and their corresponding composite ceramic powders is to develop composite ceramic powders with high expansion coefficients, low dielectric constants, and low dielectric losses. The reason why LTCC substrate materials with high thermal expansion coefficients are needed is that the ball ball array packaging (CBGA) technology has been widely used in chip packaging, and this process needs to solve the problem of matching the thermal expansion coefficients of LTCC substrates and printed circuit boards (generally PCBs with high thermal expansion coefficients).
[0003] However, among the existing patent technologies, there are very few LTCC substrate materials or composite ceramic powders that can simultaneously meet the above-mentioned performance requirements such as high thermal expansion coefficient, low dielectric constant and low dielectric loss.
[0004] U.S. Patent No. 5258335 (1993) published three types of LTCC ceramic powders: single calcium borosilicate (CBS1) glass-ceramic; composite of two calcium borosilicate glass-ceramics (CBS2+CBS3); calcium borosilicate glass-ceramic (CBS4) + borosilicate amorphous glass (BS1) + nucleating agent (CaB2O4). For the first case, single CBS1 (60wt% CaO+20wt% B2O3+20wt% SiO2) glass-ceramic was found to have a high thermal expansion coefficient (11.21×10 -6 / ℃(20-500℃)), but the corresponding dielectric properties are poor. For the second case, that is, the composite of two calcium borosilicate glass-ceramics, although the dielectric properties are good, there is no excessively high thermal expansion coefficient. For the third case, its dielectric constant is less than 7, and the dielectric loss is less than 0.003(@1MHz), but its thermal expansion coefficient is generally not high. Another composite ceramic powder (CBS5+20%FS) has a relatively high thermal expansion coefficient (10.19×10 -6 / ℃(20℃-500℃)), but the FS at this time is amorphous fused quartz (high melting process difficulty) rather than easy-to-melt borosilicate glass. Different CBS glass-ceramics have different content ratios of CaO, B2O3 and SiO2, and the melting temperature of amorphous borosilicate glass (BS1) is higher, and its composition is (mass percentage): 71% SiO2, 26% B2O3, 0.5% Na2O, 1% K2O, 0.5% Li2O, 1wt% Al2O3.
[0005] Patent CN 101077835A (2007) discloses a composite porcelain powder, which contains 46-90wt% calcium borosilicate glass, 6-50wt% borosilicate glass and 0.5-5wt% nucleating agent. The calcium borosilicate glass is composed of 30-50wt% CaO, 10-30wt% B2O3, 30-55wt% SiO2, while the borosilicate glass is composed of 65-75wt% SiO2, 20-30wt% B2O3, R2O (R=K, Na, and / or Li) 0.5-3wt%. The nucleating agent is ZrO2 and / or TiO2. Although the composite ceramic powder of the invention is similar to the second case of U.S. Pat. No. 5,258,335, both of which are composed of calcium borosilicate glass, borosilicate glass and a nucleating agent, the specific components of each part are quite different; similarly, the composite ceramic powder has a dielectric constant of 5-6.85 and a relatively low dielectric loss (0.0023@10GHz), but its thermal expansion coefficient (<10.8×10 -6 / ℃(20-400℃)) is still not ideal.
[0006] CN106045323 (2016) discloses a composite porcelain powder comprising 35-75wt% of a composite oxide and 25-65wt% of quartz (ceramic phase), wherein the composition of the composite oxide is: 20-65wt% CaO, 5-15wt% B2O3, 20-55wt% SiO2, 0-10wt% Al2O3, 0-10wt% ZrO2, 0-2wt% Cr2O3 / Co2O3. The composite oxide is prepared by batching, mixing and pre-firing (firing at 600-800°C for 1-4h), rather than by glass melting. The composition and process of the porcelain powder of the patent invention are quite different from those of the above two patents. The dielectric loss (<0.001) and thermal expansion coefficient ((8.5-12.5)×10 -6 / ℃) meets the requirements, but the corresponding dielectric constant (5-6.5) is not low enough.
[0007] CN110357597 (2019) uses a mixture of oxides as a porcelain powder, the composition of which is 10-40wt% CaO, 3-12wt% B2O3, 50-70wt% SiO2, 2-5wt% Al2O3, 3-10wt% CuO / ZrO2. Like the above-mentioned patent CN106045323, the porcelain powder of this patent is not subjected to a glass melting process, but is made by a calcination process at 600-800°C. The dielectric constant obtained with this porcelain powder is 5.4-5.8@1-10GHz, the dielectric loss is <0.004@1-10GHz, and the thermal expansion coefficient is (10-11)×10 -6 / ℃. The higher thermal expansion coefficient is related to the main crystalline phases precipitated in the material, namely wollastonite and quartz, but the resulting dielectric constant is still not low enough.
[0008] US10562809 (2022) discloses a new composite ceramic powder containing 10-99wt% amorphous quartz glass or crystalline silica ceramic phase and 1-90wt% borosilicate glass phase. The composite ceramic powder is characterized by a generally low dielectric constant (<8@10-30GHz) and a low dielectric loss (<0.002@10-30GHz). When the crystalline silica is cristobalite (having a high thermal expansion coefficient), a high thermal expansion coefficient (12.45×10 -6 / °C). The composition (molar percentage) of the glass phase is: 50-90mol% SiO2, 0.1-35mol% B2O3, 0.1-25mol% Al2O3, 0.1-10mol% K2O, 0.1-10mol% Na2O, 0.1-20mol% Li2O, 0.1-30mol% F, and the sum of Li2O, Na2O and K2O is 0.1-30mol%. However, the sintering temperature of the composite ceramic powder is as high as 950°C or 1100°C, which is not an ideal LTCC sintering temperature, and the combination of borosilicate glass and silicon dioxide (ceramic phase) is different from the combination of borosilicate glass and microcrystallizable calcium borosilicate glass.
[0009] The characteristics of the above-mentioned patents are compared in Table 1.
[0010] Table 1 Summary of main features of existing published patents
[0011]
[0012] It can be seen that the ceramic powders involved in the existing patented technologies cannot simultaneously meet the performance requirements of LTCC substrates with high thermal expansion coefficient, low dielectric constant and low dielectric loss, and there are problems such as complex raw material composition and too high sintering temperature. Therefore, the development of LTCC substrate materials or composite ceramic powders with excellent comprehensive performance, simple composition and easy sintering has become a technical problem that needs to be solved urgently. Summary of the invention
[0013] The object of the present invention is to provide a composite ceramic powder for LTCC substrates which can meet the performance requirements of low dielectric, low loss and high expansion LTCC substrates, can be sintered at low temperature to form a compact structure, contains microcrystallizable glass and borosilicate glass, and does not contain an external nucleating agent and a ceramic phase.
[0014] The first purpose of the present invention is to provide a composite ceramic powder for high expansion, low dielectric and low loss LTCC substrates, the composite ceramic powder comprising 50-60wt% borosilicate glass powder and 40-50wt% calcium borosilicate glass powder, preferably, the particle size D50 of the borosilicate glass powder and the calcium borosilicate glass powder are both 1.0-2.5μm, and both are amorphous (not crystallized). Too large a particle size will affect the sintering density of the composite ceramic powder, while too small a particle size will increase the production cost and reduce the dispersibility of the powder in the slurry for tape casting;
[0015] The borosilicate glass powder comprises the following components by mass percentage: SiO2 55-63%, Al2O3 3-5%, CaO 3-5%, BaO 1.5-3%, B2O3 20-26%, ZnO 2-5%, MgO 0.5-1.5%, TiO2 0.5-1.5%, SrO 0.1-1%, ZrO2 0.1-1%;
[0016] Calculated by mass percentage, the calcium borosilicate glass powder comprises the following components: CaO 36-42%, B2O3 15-20%, SiO2 36-42%, BaO 0.5-1.2%, ZnO 0.5-1.2%, ZrO2 0.5-1.0%, La2O3 0.1-0.5%, TiO2 0.1-0.5%, and CaF2 0.1-0.5%.
[0017] The components of the calcium borosilicate glass and borosilicate glass involved in the present invention are greatly different from those in other patents. The SiO2 content of the borosilicate glass of the present invention is low, that is, not higher than 63wt%, while the SiO2 content of the borosilicate glass used in U.S. Patent US5258335 is 71wt%, and the SiO2 content of the borosilicate glass used in Chinese Patent CN 101077835A is 75wt%. Therefore, the melting temperature of the borosilicate glass of the present invention is relatively low, and the glass liquid is easy to pour or flow out of the crucible, which meets the requirements of mass production of glass liquid.
[0018] The second object of the present invention is to provide a method for preparing the aforementioned high expansion, low dielectric, low loss LTCC substrate composite ceramic powder, comprising the following steps:
[0019] (1) Preparation of borosilicate glass powder:
[0020] (a1) Weighing SiO2, Al2O3, ZnO, MgO, TiO2, ZrO2, CaCO3, BaCO3, SrCO3, and H3BO3 respectively for use; wherein CaCO3, BaCO3, SrCO3, and H3BO3 are used as precursors of CaO, BaO, SrO, and B2O3, respectively, and the mass conversion between the precursors and the corresponding oxides is based on keeping the molar number of the element Ca, Ba, Sr, or B in the molecule equal;
[0021] (a2) dry-grinding the raw materials to obtain a mixture; smelting the mixture at a high temperature, preferably 1500-1560° C. for 120-240 min, to obtain molten glass; pouring the molten glass into deionized water for quenching to obtain glass pieces; ball-milling the glass pieces to obtain borosilicate glass powder;
[0022] (2) Preparation of calcium borosilicate glass powder:
[0023] (b1) Weighing SiO2, ZnO, La2O3, TiO2, ZrO2, CaF2, CaCO3, BaCO3, and H3BO3 respectively for later use; wherein CaCO3, BaCO3, and H3BO3 are used as precursors of CaO, BaO, and B2O3, respectively, and the mass conversion between the precursors and the corresponding oxides is based on keeping the molar number of the element Ca, Ba, or B in the molecule equal;
[0024] (b2) dry-grinding the raw materials to obtain a mixture; smelting the mixture at high temperature, preferably at 1400-1450° C. for 90-180 min, to obtain molten glass; pouring the molten glass into deionized water for quenching to obtain glass pieces; drying the glass pieces, preferably at 90-120° C., and then ball-milling the glass pieces to obtain calcium borosilicate glass powder;
[0025] (3) Preparation of composite porcelain powder: borosilicate glass powder and calcium borosilicate glass powder are weighed separately and mixed evenly to obtain the composite porcelain powder.
[0026] The third object of the present invention is to provide a high expansion, low dielectric and low loss LTCC substrate, the raw materials for its preparation include the aforementioned composite ceramic powder. Specifically, according to conventional processes, the composite powder can be mixed with an organic carrier to form a slurry, and then cast to obtain a green ceramic tape, which is then debonded and sintered.
[0027] The fourth object of the present invention is to provide the use of the aforementioned composite ceramic powder in the preparation of a high expansion, low dielectric, and low loss LTCC substrate.
[0028] The beneficial effects of the present invention are:
[0029] The composite ceramic powder provided by the present invention can obtain excellent dielectric properties and high thermal expansion coefficient after molding or pressing, debinding and sintering. Specifically, the dielectric constant ranges between 4.2-5.0, the dielectric loss is 0.001-0.002@12-15GHz, and the thermal expansion coefficient is (11-12)×10 -6 The composite ceramic powder can be sintered to a high density at 870-900°C and within 40-120 min (heating rate is 2-5°C / min), and the sintered density is 2.45-2.65 g / cm 3 , the sintering shrinkage is 15-18%. In other words, the present invention has the characteristics of low dielectric, low loss, high expansion, low temperature sintering and compactness, containing microcrystallizable glass and borosilicate glass and no external nucleating agent and ceramic phase. The composite ceramic powder of the present invention has excellent comprehensive performance, simple composition, and is easy to sinter, so it is more suitable for matching packaging with high expansion substrates (such as PCB). BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the thermal expansion curve of the sintered body of the composite ceramic powder of Example 3 of the present invention;
[0031] Figure 2 The X-ray diffraction spectrum of the composite ceramic powder of Example 3 of the present invention after sintering at 900° C. at room temperature;
[0032] Figure 3 This is a secondary electron scanning microscope (SEM) photograph of the fracture of the composite ceramic powder of Example 3 of the present invention after sintering at 900° C.;
[0033] Figure 4 is the thermal expansion curve of the sintered body of Comparative Example 1;
[0034] Figure 5 This is the thermal expansion curve of the sintered body of Comparative Example 2. DETAILED DESCRIPTION
[0035] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0036] The formulas of various embodiments and comparative examples of borosilicate glass powder are summarized in Table 2.
[0037] Table 2 Borosilicate glass powder examples and comparative examples
[0038]
[0039]
[0040] The formulas of various embodiments and comparative examples of calcium borosilicate glass powder are summarized in Table 3.
[0041] Table 3 Calcium borosilicate glass powder embodiment and comparative example formula
[0042]
[0043] The formulas of various embodiments and comparative examples of composite ceramic powder for LTCC are summarized in Tables 4 to 6.
[0044] Table 4 Composite Porcelain Powder Example Formula
[0045]
[0046] Table 5 Composite Porcelain Powder Comparative Example Formula (I)
[0047]
[0048] Table 6 Composite Porcelain Powder Comparative Example Formula (II)
[0049]
[0050] The formula of "equivalent ingredients of the composite powder of Example 3c" in Comparative Example 4 is shown in Table 7.
[0051] Table 7 Equivalent composition formula of composite powder of Example 3c
[0052]
[0053] The preparation methods of the composite ceramic powders in the above embodiments and comparative examples are described in detail as follows:
[0054] Example 1c
[0055] A composite ceramic powder for a high expansion, low dielectric, and low loss LTCC substrate, the preparation method of which is as follows:
[0056] (1) Preparation of borosilicate glass powder:
[0057] According to the ratio of oxides in Example 1a in Table 2, the weight of each raw material required to prepare 250g of borosilicate glass powder was calculated, and then analytically pure (>=99%) oxides (SiO2, Al2O3, ZnO, MgO, TiO2, ZrO2) and oxide precursors (CaCO3, BaCO3, SrCO3, H3BO3) were weighed and set aside; among them, CaCO3, BaCO3, SrCO3, and H3BO3 were used as precursors of CaO, BaO, SrO, and B2O3, respectively, and the mass conversion was based on keeping the molar number of elements Ca, Ba, Sr, and B constant, for example , 2 moles of H3BO3 are needed to obtain 1 mole of B2O3 in the glass, or 1.776 units of H3BO3 (boric acid) are needed to obtain 1 unit weight of B2O3 (boron trioxide); a horizontal ball mill is used to dry mix the raw materials, and then a corundum mullite crucible is used to load the mixture, and the electric furnace is heated to 1500°C for 308 minutes, and maintained at this temperature for 240 minutes to homogenize the glass liquid, and then the glass liquid is poured into deionized water to obtain glass fragments, and then planetary ball milling is performed with deionized water and stabilized zirconia balls to obtain 1.0-2.5μm borosilicate glass powder;
[0058] (2) Preparation of calcium borosilicate glass powder:
[0059] According to the ratio of oxides in Example 1b in Table 3, the weight of each raw material required to prepare 250g of calcium borosilicate glass powder was calculated, and then analytically pure (>=99%) oxides (SiO2, ZnO, La2O3, TiO2, ZrO2), calcium fluoride (CaF2) and oxide precursors (CaCO3, BaCO3, H3BO3) were weighed and set aside; among them, CaCO3, BaCO3, and H3BO3 were used as precursors of CaO, BaO, and B2O3, respectively, and based on keeping Ca, B The mass conversion is performed by keeping the molar numbers of a and B constant; dry mixing the raw materials with a planetary ball mill, and then using a platinum crucible to hold the mixture for standby use, and when the temperature of the electric furnace rises to 1400° C., the platinum crucible filled with the mixture is sent into the electric furnace and kept warm for 180 minutes to homogenize the glass liquid, and then the glass liquid is poured into deionized water to obtain glass fragments, and then the glass slag is dried in an oven at 90° C., and finally planetary ball milling is performed with anhydrous ethanol and stabilized zirconium oxide balls to obtain 1.0-2.5 μm calcium borosilicate glass powder;
[0060] (3) Preparation of composite porcelain powder: According to the ratio of Example 1c in Table 4, 180 g of borosilicate glass powder and 120 g of calcium borosilicate glass powder were taken, and the two glass powders were dry-mixed evenly using a planetary ball mill to obtain the composite porcelain powder.
[0061] Example 2c
[0062] A composite ceramic powder for a high expansion, low dielectric, and low loss LTCC substrate, the preparation method of which is as follows:
[0063] (1) Preparation of borosilicate glass powder:
[0064] According to the ratio of oxides in Example 2a in Table 2, the weight of each raw material required to prepare 2 kg of borosilicate glass powder was calculated, and then analytically pure (>=99%) oxides (SiO2, Al2O3, ZnO, MgO, TiO2, ZrO2) and oxide precursors (CaCO3, BaCO3, SrCO3, H3BO3) were weighed and set aside; among them, CaCO3, BaCO3, SrCO3, and H3BO3 were used as precursors of CaO, BaO, SrO, and B2O3, respectively, and based on keeping the molar number of Ca, Ba, Sr, and B constant, the weight of each raw material was calculated. The mass conversion is performed without changing the fixed value; a horizontal ball mill lined with polyurethane is used to dry mix the raw materials, and then a set of corundum mullite crucibles is placed in a lifting high-temperature frit furnace, and the temperature is raised to 1560°C, and then the prepared mixture is added to the corundum mullite crucible through a ceramic funnel, and then the temperature is kept for 120 minutes to obtain a uniform glass liquid, and then the discharge port of the crucible is opened to allow the glass liquid to flow into a container filled with deionized water to obtain glass fragments, and then deionized water and stabilized zirconia balls are used for planetary ball milling, and 1.0-2.5μm borosilicate glass powder is obtained after sieving, drying and crushing;
[0065] (3) Preparation of calcium borosilicate glass powder:
[0066] According to the ratio of oxides in Example 2b in Table 3, the weight of each raw material required to prepare 2 kg of calcium borosilicate glass powder was calculated, and then analytically pure (>=99%) oxides (SiO2, ZnO, La2O3, TiO2, ZrO2), calcium fluoride (CaF2) and oxide precursors (CaCO3, BaCO3, H3BO3) were weighed and set aside; among them, CaCO3, BaCO3, and H3BO3 were used as precursors of CaO, BaO, and B2O3, respectively, and based on keeping Ca, Ba , and the molar number of B is constant for mass conversion; a planetary ball mill is used to dry mix the raw materials, and then a platinum crucible is used to hold the mixture for standby use. When the temperature of the electric furnace rises to 1400°C, the platinum crucible filled with the mixture is sent into the electric furnace and kept warm for 180 minutes to obtain a uniform glass liquid, and then the glass liquid is poured into deionized water to obtain glass fragments, and then the glass slag is dried in an oven at 120°C, and finally anhydrous ethanol and stabilized zirconia balls are used for planetary ball milling to obtain 1.0-2.5μm calcium borosilicate glass powder;
[0067] (3) Preparation of composite porcelain powder: According to the ratio of Example 2c in Table 4, 2 kg of borosilicate glass powder and 2 kg of calcium borosilicate glass powder were taken, and the two glass powders were mixed evenly using a dry stirring ball mill, and the balls and powder were separated to obtain the composite porcelain powder.
[0068] Example 3c
[0069] A composite ceramic powder for a high expansion, low dielectric, and low loss LTCC substrate, the preparation method of which is as follows:
[0070] (1) Preparation of borosilicate glass powder:
[0071] According to the ratio of oxides in Example 3a in Table 2, the weight of each raw material required to prepare 168g of borosilicate glass powder was calculated, and then analytically pure (>=99%) oxides (SiO2, Al2O3, ZnO, MgO, TiO2, ZrO2) and oxide precursors (CaCO3, BaCO3, SrCO3, H3BO3) were weighed and set aside; among them, CaCO3, BaCO3, SrCO3, and H3BO3 were used as CaO, BaO, SrCO3, and H3BO3, respectively. O, B2O3 precursor, and based on keeping the molar number of Ca, Ba, Sr, B constant, the mass conversion is performed; the raw materials are dry mixed in a horizontal ball mill, and then the mixed material is placed in a corundum mullite crucible, put into a muffle furnace, heated to 1540°C, and kept warm for 180 minutes to obtain a uniform glass liquid, and then the glass liquid is poured into deionized water to obtain glass fragments, and then planetary ball milling is performed with deionized water and stabilized zirconia balls to obtain 1.5-2.5μm borosilicate glass powder;
[0072] (2) Preparation of calcium borosilicate glass powder:
[0073] According to the ratio of oxides in Example 3b in Table 3, the weight of each raw material required to prepare 132g of calcium borosilicate glass powder was calculated, and then analytically pure (>=99%) oxides (SiO2, ZnO, La2O3, TiO2, ZrO2), calcium fluoride (CaF2) and oxide precursors (CaCO3, BaCO3, H3BO3) were weighed and set aside; wherein CaCO3, BaCO3, and H3BO3 were used as precursors of CaO, BaO, and B2O3, respectively, and based on maintaining Ca, Ba, and B The mass conversion is performed by keeping the number of moles constant; a planetary ball mill is used to dry mix the raw materials, and then a platinum crucible is used to load the mixture, but when the temperature of the muffle furnace reaches 1200°C, the crucible containing the mixture is placed, and the temperature is continued to rise to 1450°C, and then maintained at this temperature for 90 minutes to obtain a uniform glass liquid, and then the glass liquid is poured into deionized water to obtain glass fragments, and then the glass slag is dried in an oven at 120°C, and finally anhydrous ethanol and stabilized zirconia balls are used for planetary ball milling to obtain 1.5-2.5μm calcium borosilicate glass powder;
[0074] (3) Preparation of composite porcelain powder: According to the ratio of Example 3c in Table 4, 168 g of borosilicate glass powder and 132 g of calcium borosilicate glass powder were taken, and the two glass powders were mixed evenly using a horizontal planetary ball mill, and the grinding balls and the mixed powder were separated to obtain the composite porcelain powder.
[0075] Comparative Example 1
[0076] Preparation method: Same as step (2) of Example 3c.
[0077] Comparative Example 2
[0078] Preparation method: Same as step (1) of Example 3c.
[0079] Comparative Example 3
[0080] Preparation method: The only difference from Example 3c is that in the composite porcelain powder, the composition ratio of borosilicate glass powder and calcium borosilicate glass powder is different. In this comparative example, the borosilicate glass powder and calcium borosilicate glass powder are 189g and 111g, respectively.
[0081] Comparative Example 4
[0082] Preparation method: According to the ratio of oxides in Table 7, calculate the weight of each raw material required to prepare 300g of composite porcelain powder, then weigh analytically pure (>=99%) oxides (SiO2, Al2O3, ZnO, La2O3, TiO2, MgO, ZrO2), calcium fluoride (CaF2) and oxide precursors (CaCO3, BaCO3, SrCO3, H3BO3). Use a planetary ball mill to dry mix the raw materials (3-4h@250-260rpm), then use a 300mL corundum mullite crucible to load the mixture, put it into a muffle furnace, heat it to 1540℃ in 300min and keep it warm for 90min to obtain glass liquid, and then pour the glass liquid into deionized water to obtain glass fragments.
[0083] Comparative Example 5
[0084] Preparation method: According to the ratio of comparative example 5 in Table 6, silicon micropowder (quartz) with a median diameter of 2-2.5 μm and the calcium borosilicate glass powder of Example 3b with a lower sintering temperature are mixed evenly using a horizontal planetary ball mill to obtain.
[0085] Comparative Example 6
[0086] Preparation method: According to the ratio of comparative example 6 in Table 6, silicon micropowder (quartz) with a median diameter of 2-2.5 μm and borosilicate glass powder of Example 3a with a higher sintering temperature are mixed evenly using a horizontal planetary ball mill to obtain.
[0087] Experimental example
[0088] 1. Performance test of the composite ceramic powder of the present invention
[0089] 1.1 Sample preparation: This sample preparation method is applicable to the examples or comparative examples. Example 3c is now used as an example to illustrate that the composite porcelain powder prepared in Example 3c is mixed with anhydrous ethanol (1:1.2 weight ratio) to obtain a slurry, and then a binder (polyethylene oxide, 0.25-0.35% of the powder weight), a plasticizer (polyethylene glycol, 3-3.5% of the powder weight) and a release agent (stearic acid, 0.2-0.3% of the powder weight) are added to the slurry, and the powder is mixed and refined by planetary ball milling for 40 minutes (rotation speed 250-260rpm), dried at 70°C, dry ball milled, and passed through a 60-mesh sieve to form a manual granulation powder. The granulation powder is dry pressed under a pressure of 100-150MPa, and a long rectangular sample four-open steel mold and a cylindrical sample steel mold are respectively used according to the shape and size requirements of the test sample. The binder was removed at 500°C for 3 h, and the heating rate from room temperature to 500°C was 3-4°C / min. The temperature was further raised to 870-900°C, and the holding time was 40-120 min, wherein the heating rate was <3°C / min, and a dense sintered light white sample was obtained.
[0090] 1.2 Sample performance test and structural analysis method:
[0091] 1.2.1 The sintered density is measured by the water displacement method based on Archimedes' principle: first measure the weight W of the sample, then measure the weight W1 of the sample in deionized water, then measure the weight W2 of the sample after removing the water on the surface of the sample, and finally calculate the sample density according to the following formula: sintered density = (W × 1g / cm 3 ) / (W2-W1).
[0092] 1.2.2 The calculation of the sample sintering shrinkage rate is based on the relative change of a certain dimension of the sample after sintering relative to the original green body size, that is, sintering shrinkage rate = (sintered sample size - green body sample size) × % / green body sample size.
[0093] 1.2.3 The thermal expansion coefficient of the sintered sample is measured using a thermal expansion instrument. The sample needs to be cut into 5×5×20 (mm) strip samples using a diamond cutting blade (although the standard sample requires a cylindrical shape of 5mm in diameter × 20mm in length, long cylindrical samples are difficult to process and have high processing costs), and then the four edges of the sample strip are ground off, and finally the thermal expansion curve of the sample is measured.
[0094] 1.2.4 The dielectric properties of the sintered samples were measured using the resonant cavity method. After sintering, the sample was a small cylinder with a height slightly greater than half of the cylinder diameter. The diameter of the green compact mold used was 12 mm, and the height of the green compact mainly depended on the weight of the powder.
[0095] 1.3 Test results:
[0096] The sintered density of the sample in Example 3c is 2.55-2.62 g / cm 3 The sintering shrinkage is 16-18%. The dielectric constant is between 4.2-4.5, and the dielectric loss is 0.001-0.0015@12-15GHz. The thermal expansion curve is as follows Figure 1 As shown in the curve, it can be read that the relatively high average thermal expansion coefficient in the range of 30-500℃ is 11.6×10 -6 / ℃, it can also be seen that the sintered body has two softening points, which are ~600℃ and 755℃ respectively. A thermal expansion curve has two softening points, indicating that there are two residual glass phases in the sintered body, which is related to the original borosilicate glass powder (BS) and calcium borosilicate glass powder (CBS) glass phases in the composite porcelain powder, but not necessarily the original unchanged BS and CBS glass phases. The test results of Example 3c and other examples and comparative examples are listed in Tables 8 and 9.
[0097] Table 8 Summary of sample performance test results (I)
[0098]
[0099] Table 9 Summary of sample performance test results (II)
[0100] Glass Type Process and performance description Comparative Example BS-1 The glass liquid has high viscosity and is not easy to produce glass Comparative Example BS-2 The glass melting temperature is high, and the glass liquid is difficult to flow out of the crucible Comparative Example BS-3 The glass is easily hydrolyzed and cannot be ball-milled with water medium. Comparative Example CBS-1 It is not easy to form glass-ceramics, resulting in high dielectric loss, >0.005 Comparative Example CBS-2 Sintering temperature is higher than 900℃ Comparative Example CBS-3 Difficult to sinter, sintered body swells
[0101] 2. Microstructure analysis of composite ceramic powder sintered body
[0102] In order to understand why the sample has such a high thermal expansion coefficient after sintering, an X-ray diffractometer (XRD) was used to analyze the crystalline phase in the composite porcelain powder sample after sintering. First, the composite porcelain powder of Example 3c was placed loosely (without pressing) in a corundum crucible, and then heated to 870-900℃ for 40-120min, with a heating rate of <3℃ / min. Finally, the sintered block was crushed and dry-milled to obtain a powder sample with a particle size of less than 45μm. The diffraction peaks of the sample XRD are as follows: Figure 2 As shown. The horizontal axis is the diffraction angle 2Theta (unit: °), and the vertical axis is the diffraction line intensity (unit: cps). The spectrum shows that a crystalline phase has precipitated from the original amorphous glass BS and CBS complex, and the crystalline phase is determined to be quartz (the standard phase data file number is PDF 46-1045). Due to the high thermal expansion coefficient of quartz (~14×10 -6 / ℃), so the precipitation of quartz in the composite glass system leads to a high thermal expansion coefficient of the sintered body (microcrystalline glass or glass ceramics).
[0103] Analysis: Compared with calcium borosilicate glass powder (Example 3b), borosilicate glass powder (Example 3a) contains higher SiO2, and the content of borosilicate glass powder in the composite porcelain powder is high, so the precipitated quartz phase can be regarded as mainly coming from the borosilicate glass powder matrix, however, the borosilicate glass powder existing alone is stable below 900°C, that is, it remains in an amorphous state and will not precipitate a quartz ceramic phase. In addition, calcium borosilicate glass powder existing alone will not precipitate quartz, but wollastonite (CaSiO3) will be precipitated. Therefore, the quartz phase precipitated (not added in advance) by the composite porcelain powder of the present invention is the result of mutual diffusion and mutual reaction between calcium borosilicate glass powder and borosilicate glass powder at high temperature, which is also the uniqueness of the present invention.
[0104] The dielectric properties of the sample are closely related to the sintering density of the sample. Generally speaking, the dielectric loss of the densely sintered sample is lower than that of the non-densely sintered sample. Therefore, it is necessary to use a scanning electron microscope (SEM) to observe the pores inside the sintered sample (such as the fracture). Figure 3 As shown, it can be seen that the sintered body is relatively dense, that is, the pores are relatively small and few.
[0105] 3. Other experimental research
[0106] 3.1 The sintered bodies of the ceramic powders of Comparative Example 1 (Example 3b) and Comparative Example 2 (Example 3a) were prepared by referring to the method for preparing the composite ceramic powder sintered body of Example 3c above, but the sintering temperature was reduced to 860°C and kept at this temperature for 20 minutes. The thermal expansion curves were measured as follows: Figure 4 and Figure 5 From the thermal expansion curve of the sintered ceramic powder of Comparative Example 1, it can be read that the average thermal expansion coefficient in the range of 30-500°C is 8.48×10 -6 / ℃, which is not high. From the thermal expansion curve of the sintered ceramic powder in Comparative Example 2, it can be read that the average thermal expansion coefficient in the range of 30-500℃ is 4.5×10 -6 / ℃, which belongs to the low thermal expansion coefficient level. It can be seen that when borosilicate glass powder or calcium borosilicate glass powder is used alone, the sintered body cannot obtain a high thermal expansion coefficient.
[0107] 3.2 Comparative Example 3 The experiment found that due to the high softening point (about 775°C) borosilicate glass content of Example 3a, accounting for 63wt%, the composite porcelain powder has poor sintering properties, which is manifested in the loose fracture of the sample and the large number of micropores.
[0108] 3.3 Comparative Example 4 Experiments show that although glass liquid can be produced, it is easy to lose transparency (not crystal clear glass), but milky white glass slag, which is an abnormal phenomenon of glass melting, indicating that the glass liquid is difficult to form glass, but easy to undergo phase separation or crystallization, and the acquisition of microcrystalline glass must start from amorphous glass. It can be seen that the composite ceramic powder of the present invention cannot be prepared by directly mixing all components, but needs to be made into two glass powders separately and then mixed.
[0109] 3.4 The ceramic powders of Comparative Example 5 and Comparative Example 6 were respectively ball-milled with alcohol for 1 hour, dried, broken up, sieved, pressed, and sintered at 900°C for 60 minutes. It was found that the sintering shrinkage of Comparative Example 5 was only 4.5-4.9%, and the sintered body was not formed into porcelain, or the density was poor. If the sintering density is to be improved, the content of silicon micropowder must be greatly reduced, but this is not conducive to the improvement of the thermal expansion coefficient. The density of Comparative Example 6 is even worse. This means that, compared with the composite porcelain powder formed by two special glass powders used in the present invention, the sintered body density of the composite porcelain powder obtained by adding quartz powder (rather than the quartz phase precipitated from the matrix glass) is poor. Although quartz powder can increase the thermal expansion coefficient, it also deteriorates the sintering density of the composite porcelain powder, resulting in dielectric properties that do not meet the requirements. The present invention uses two amorphous glass powders which have relatively good dielectric properties but relatively low thermal expansion coefficients, and obtains a new high-density microstructure containing a precipitated quartz phase through composite and reaction sintering. As a result, the composite porcelain powder sintered body has good comprehensive properties, which meets the strict requirements of low dielectric, low loss and high expansion of LTCC ceramic substrates.
[0110] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A composite ceramic powder for high expansion, low dielectric and low loss LTCC substrate, characterized in that: The composite porcelain powder comprises 50-60wt% of borosilicate glass powder and 40-50wt% of calcium borosilicate glass powder; The borosilicate glass powder comprises the following components by mass percentage: SiO2 55-63%, Al2O3 3-5%, CaO 3-5%, BaO 1.5-3%, B2O3 20-26%, ZnO 2-5%, MgO 0.5-1.5%, TiO2 0.5-1.5%, SrO 0.1-1%, ZrO2 0.1-1%; The calcium borosilicate glass powder comprises the following components by mass percentage: CaO 36-42%, B2O3 15-20%, SiO2 36-42%, BaO 0.5-1.2%, ZnO 0.5-1.2%, ZrO2 0.5-1.0%, La2O3 0.1-0.5%, TiO2 0.1-0.5%, CaF2 0.1-0.5%; The particle size D50 of the borosilicate glass powder and the calcium borosilicate glass powder are both 1.0-2.5 μm, and both are amorphous.
2. The method for preparing the composite ceramic powder for high expansion, low dielectric and low loss LTCC substrate according to claim 1, characterized in that: The steps include: (1) Preparation of borosilicate glass powder: (a1) Weighing SiO2, Al2O3, ZnO, MgO, TiO2, ZrO2, CaCO3, BaCO3, SrCO3, and H3BO3 respectively for use; wherein CaCO3, BaCO3, SrCO3, and H3BO3 are used as precursors of CaO, BaO, SrO, and B2O3, respectively, and the mass conversion between the precursors and the corresponding oxides is based on keeping the molar number of the element Ca, Ba, Sr, or B in the molecule equal; (a2) dry-grinding the raw materials to obtain a mixture; melting the mixture at high temperature to obtain molten glass; pouring the molten glass into deionized water for quenching to obtain glass pieces; ball-milling the glass pieces to obtain borosilicate glass powder; (2) Preparation of calcium borosilicate glass powder: (b1) Weighing SiO2, ZnO, La2O3, TiO2, ZrO2, CaF2, CaCO3, BaCO3, and H3BO3 respectively for later use; wherein CaCO3, BaCO3, and H3BO3 are used as precursors of CaO, BaO, and B2O3, respectively, and the mass conversion between the precursors and the corresponding oxides is based on keeping the molar number of the element Ca, Ba, or B in the molecule equal; (b2) dry-grinding the raw materials to obtain a mixture; melting the mixture at high temperature to obtain molten glass; pouring the molten glass into deionized water for quenching to obtain glass pieces; drying the glass pieces and then ball-milling them to obtain calcium borosilicate glass powder; (3) Preparation of composite porcelain powder: borosilicate glass powder and calcium borosilicate glass powder are weighed separately and mixed evenly to obtain the composite porcelain powder.
3. The method for preparing the composite ceramic powder for high expansion, low dielectric and low loss LTCC substrate according to claim 2, characterized in that: In step (a2), the high temperature smelting temperature is 1500-1560°C and the time is 120-240 minutes.
4. The method for preparing the composite ceramic powder for high expansion, low dielectric and low loss LTCC substrate according to claim 2, characterized in that: In step (b2), the high temperature smelting temperature is 1400-1450°C and the time is 90-180 minutes.
5. The method for preparing the composite ceramic powder for high expansion, low dielectric and low loss LTCC substrate according to claim 2, characterized in that: In step (b2), the glass cullets are dried at 90-120°C.
6. A high expansion, low dielectric, low loss LTCC substrate, characterized in that: The raw materials for preparing the composite porcelain powder include the composite porcelain powder described in claim 1.
7. Use of the composite ceramic powder according to claim 1 in preparing a high expansion, low dielectric, and low loss LTCC substrate.
Citation Information
Patent Citations
High-frequency low-loss low-temperature co-burning ceramic raw material tape and preparation method thereof
CN101077835A
Low K dielectric compositions for high frequency applications
US10562809B2
Low dielectric, low temperature fired glass ceramics
US5258335A
Dielectric constant series adjustable glass powder for low-dielectric-constant LTCC material and preparation method of glass powder
CN112624617A